Ending Gender-Based Sexual Violence on Canadian Campuses: Peer Educator Perspectives - Laker, Jason A. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
Gender-based and sexual violence (GBSV) remains a pervasive problem in higher education, disproportionately affecting marginalized students and undermining their safety, well-being, and academic success. Post-secondary institutions (PSIs) increasingly rely on peer educators (PeerEds) to deliver prevention and response programs, leveraging their shared student experience to foster trust and engagement. This study explores the motivations and experiences of GBSV PeerEds in Canada and the United States, revealing how personal trauma, institutional critique, and allyship drive their involvement. Findings highlight the emotional labour, secondary trauma, and systemic constraints PeerEds face, alongside their contributions to campus culture and advocacy. The study critiques institutional reliance on marginalized students’ compassion and calls for trauma-informed practices, sustainable funding, and structural reform. Future research should examine PeerEds’ influence on campus subcultures, administrators’ complicity, and the broader legitimacy of peer-led GBSV initiatives. Meaningful change requires confronting institutional complicity and reimagining ethics of care.